2023
DOI: 10.3389/fendo.2023.1306470
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin D supplementation on metabolic parameters, serum irisin and obesity values in women with subclinical hypothyroidism: a double-blind randomized controlled trial

Sara Safari,
Maryam Rafraf,
Mahsa Malekian
et al.

Abstract: PurposeSubclinical hypothyroidism is an early, mild form of hypothyroidism that may progress to overt hypothyroidism if untreated. The current study aimed to assess the effects of vitamin D supplementation on hormonal (thyroid stimulating hormone [TSH], triiodothyronine, thyroxine, and free thyroxine) parameters, lipid profiles, serum irisin, and obesity indices in women with subclinical hypothyroidism.MethodsThe present randomized, double-blind, placebo-controlled clinical trial was carried out on 44 women wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In 2016, in a randomized placebo-controlled trial conducted on 511 subjects with prediabetes, Jorde also found a significant decrease in LDL-C in the vitamin D supplementation group [ 116 ]. Moreover, the most recent papers show conflicting results on the effect of vitamin D supplementation on dyslipidemia [ 117 , 118 , 119 ]. Table 2 describes the main characteristics of interventional studies.…”
Section: Resultsmentioning
confidence: 99%
“…In 2016, in a randomized placebo-controlled trial conducted on 511 subjects with prediabetes, Jorde also found a significant decrease in LDL-C in the vitamin D supplementation group [ 116 ]. Moreover, the most recent papers show conflicting results on the effect of vitamin D supplementation on dyslipidemia [ 117 , 118 , 119 ]. Table 2 describes the main characteristics of interventional studies.…”
Section: Resultsmentioning
confidence: 99%
“…It increases the production of anti-inflammatory cytokines (e.g., IL-10) and T-cell inhibitory molecules (programmed death-1, PD-1), and inhibits the secretion of pro-inflammatory cytokines IL-12, IL-23, TNF-α and IFN-γ, which are involved in the differentiation of T helper cells: Th1 and Th17 [62,63]. According to available literature, vitamin D supplementation may significantly lower TSH and total cholesterol levels, as well as reduce fat mass percentage, increasing irisin levels and fat-free mass percentage in women with subclinical hypothyroidism [64]. According to systematic review and metaanalysis of 12 studies, performed by a group of Tang et al, vitamin D supplementation caused the reduction of anti-TPO and anti-TG antibodies in patients with HT.…”
Section: Vitamin Dmentioning
confidence: 99%